THE (TRANS)FORMATIVE POTENTIAL OF THE BIBLE AS RESOURCE FOR CHRISTIAN ETHOS AND ETHICS - Mouton, Elna (Scriptura, 1997)
Many Christians worldwide are currently rediscovering the power of Scripture for their practical lives. The essay argues that the transformative potential of these writings (their continuing authority and relevance in changing times and circumstances) lies in their ability to disclose an alternative moral world, a radically new perspective on reality, a new way of living in the world. Though embedded within patriarchal value systems, the intended rhetorical functions of these documents imply major shifts in the orientation (vision of humanity) and language of their readers. How is this accomplished? With the continual reference to the metaphorical 'world' of the Judaeo-Christian story, they emphasise collective memory as a major recycling strategy toward the development of the faith communities' moral identity and ethos, with healing and wholeness as major substance of their present and future hope. Through liturgy, where the vision of God's presence in the world isformed and nurtured (via the persuasive strategies of identification, alienation and reorientation), Scripture continues to invite contemporary Christian believers to re-imagine and redefine their identity, and (to faithfully choose) to grow toward the full body of Christ - i.e. beyond all limited and stereotypical views of humanity. In a co-operative shared work, Spirit, texts and readers thus engage in a transformingprocess (l1ziselton).